Role of Human Chorionic Gonadotropin in Suppression of Preterm Labor - Amber Mughis, Fauzia Anbreen, Maria Ghafoor, Najma Farhat, Kiran Javed, Rubina Babar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the mean prolongation of pregnancy via human Chorionic gonadotropin (H.C.G) in patients presenting with preterm labor. Materials and methods: This descriptive case study was conducted in obstetrics and gynecology department, Women and children teaching hospital Dera Ismail khan from October 21, 2019, to April 20, 2020. Result: A total of 123 pregnant women with preterm labor were included in the study. Average age was 25.44 years+4.70sd with range 16-35 years. Prolongation of pregnancy by human chorionic gonadotropin (HCG) of more than 30 days. Fifty-eight (47.2%) of preterm women were observed with prolongation of pregnancy of less than 30 days. Practical implication: Suppression of Preterm Labor in the females using H.C.G. Conclusion: The trial concluded that HCG is the better option in the prolongation of pregnancy in women with preterm delivery. Keywords: Preterm delivery, Prolongation of pregnancy, NICU.